1985
DOI: 10.1111/j.1365-2125.1985.tb05082.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two slow‐release formulations of metoprolol with conventional metoprolol and atenolol in hypertensive patients.

Abstract: 1 We have compared the P-adrenoceptor blocking and antihypertensive effects of chronic once daily treatment with conventional metoprolol 200 mg, two 'long-acting' formulations of metoprolol 200 mg and atenolol 100 mg in a cross-over study in 12 hypertensive patients concurrently receiving diuretic therapy. 2 The peak effects of all compounds were similar, with significant reductions in exercise heart rate and blood pressure. 3 Twenty-four hours after dosing only atenolol treatment was consistently associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…There was some overlap in these data, however, which could be explained, in part, by the higher plasma concentrations of (S)-metoprolol, the pharmacologically active enantiomer, observed in EMs . Nevertheless, all PMs but only two EMs had a clinically significant degree of ,-adrenoceptor blockade (10% or more) at the end of 24 h. In addition Silas et al (1984) have reported that the hypotensive effect of metoprolol is not maintained in EMs for 24 h after a single dose. Adequate control of angina pectoris and blood pressure might therefore be achieved with once daily dosing of metoprolol in PMs, whereas most EMs will require more frequent dosing.…”
mentioning
confidence: 90%
“…There was some overlap in these data, however, which could be explained, in part, by the higher plasma concentrations of (S)-metoprolol, the pharmacologically active enantiomer, observed in EMs . Nevertheless, all PMs but only two EMs had a clinically significant degree of ,-adrenoceptor blockade (10% or more) at the end of 24 h. In addition Silas et al (1984) have reported that the hypotensive effect of metoprolol is not maintained in EMs for 24 h after a single dose. Adequate control of angina pectoris and blood pressure might therefore be achieved with once daily dosing of metoprolol in PMs, whereas most EMs will require more frequent dosing.…”
mentioning
confidence: 90%
“…However, in a study of 12 hypertensive patients, all of whom were extensive metabolisers, the 24-hour blood pressure lowering effect of metopro-101 did not reach statistical significance following once-daily treatment for 1 month with 200mg drug given as conventional tablets or in 2 slow release forms (Silas et al 1985). …”
Section: Pharmacodynamicsmentioning
confidence: 95%
“…However, in view of a lack of a significant hypotensive effect of metoprolol in extensive metabolisers at 24 hours after dosing (Silas et al 1985), once-daily dosing with metoprolol and its slow release preparations may Table II. Possible clinical consequences of polymorphic oxidation of fj-adrenoceptor antagonists (fj-blockers)…”
Section: Hypertensionmentioning
confidence: 99%
“…8 However, Freestone's group also reported that atenolol's reduction of the pulse during exercise was less at 24 h than at 3 [1/2] h after dosing. 9 The INVEST study dosed atenolol twice a day if more than 50 mg per day was needed. 10 Dr. Wallace coauthored the Multicenter Study of Perioperative Ischemia trial, which is the largest placebo-controlled trial of atenolol for perioperative ß-blockade.…”
Section: To the Editormentioning
confidence: 99%